WAVE TRANSMISSION, REFLECTION AND ENERGY LOSS OF AN ALTERNATIVELY SUBMERGED GEOTUBE BREAKWATER SUBJECTED TO REGULAR WAVES - VENGADARAMAN, SATESH (Universiti Teknologi PETRONAS, 2017)
Over the years, there are quite a number of research and studies has been done towards the cause and effect of shoreline erosion. Some researchers used hard engineering method (conventional) and others followed the soft engineering method (geosynthetic). However not every research that has been conducted leads to success as there are still a lot of gaps that needs to be filled in their research. This study will be conducted to test the effect of wave transmission, reflection and energy loss of an alternatively submerged geotextile tube (geotube) that act as semicircular breakwater when subjected to regular waves. The water when subjected to regular waves, has few hydraulic characteristics such as wave steepness Hi/L, relative wave height Hi/d, and relative submergence, d’/Hi that will be determined in order to achieve the aim at the end of the experiment. This study focus mainly on testing the physical model of geotube against the wave parameters that was mentioned above.